2017
DOI: 10.1038/cddis.2016.478
|View full text |Cite
|
Sign up to set email alerts
|

CRB3 regulates contact inhibition by activating the Hippo pathway in mammary epithelial cells

Abstract: The loss of contact inhibition is a hallmark of cancer cells. The Hippo pathway has recently been shown to be an important regulator of contact inhibition, and the cell apical polarity determinant protein CRB3 has been suggested to be involved in Hippo signalling. However, whether CRB3 regulates contact inhibition in mammary cells remains unclear, and the underlying mechanisms have not been elucidated. As shown in the present study, CRB3 decreases cell proliferation, promotes apoptosis, and enhances the format… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 58 publications
3
37
0
Order By: Relevance
“…In the current study, we found that CRB3 expression was inversely associated with tumour size (Table ), which is consistent with previous studies showing that downregulation of CRB3 expression induced breast cancer cell proliferation, whereas CRB3 overexpression inhibited proliferation of human breast cell lines . Our previous study also showed that the downregulation of CRB3 expression increased migration and invasion of breast cancer cells, whereas CRB3 overexpression inhibited migration and invasion of human breast and kidney cancer cell lines .…”
Section: Discussionsupporting
confidence: 92%
“…In the current study, we found that CRB3 expression was inversely associated with tumour size (Table ), which is consistent with previous studies showing that downregulation of CRB3 expression induced breast cancer cell proliferation, whereas CRB3 overexpression inhibited proliferation of human breast cell lines . Our previous study also showed that the downregulation of CRB3 expression increased migration and invasion of breast cancer cells, whereas CRB3 overexpression inhibited migration and invasion of human breast and kidney cancer cell lines .…”
Section: Discussionsupporting
confidence: 92%
“…We previously reported that KIBRA and PTPN14 form a complex that regulates LATS1 function [ 8 ]. In addition, it has been recently reported that the apical-basal polarity protein CRB3 interacts and stabilize KIBRA in mammary epithelial cells [ 25 ]. The mammalian KIBRA/WWC1 protein contains another two similar proteins (WWC2 and WWC3) [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several signaling pathways have been implicated in this regulation relaying density signals to induce cell-cycle arrest in response to cell contact (Polyak et al, 1994a ; Wieser et al, 1999 ; Heit et al, 2001 ; Faust et al, 2005 ; Zhao et al, 2008 ; Barry and Camargo, 2013 ; Gumbiner and Kim, 2014 ). The Hippo-YAP/TAZ pathway has been found to play important roles in contact inhibition through mechanical cues provided by the microenvironment (Zeng and Hong, 2008 ; Chen et al, 2012 ; Halder et al, 2012 ; Schroeder and Halder, 2012 ; Gumbiner and Kim, 2014 ; Mao et al, 2017 ). Discovered in Drosophila, Hippo-YAP/TAZ signaling is a conserved pathway involved in contact inhibition, mechanotransduction, proliferation, and organ size determination (Piccolo et al, 2014 ).…”
Section: Information Provided By the Tissue Architecture And Geometrymentioning
confidence: 99%